Assessment of Knowledge and Attitude of Adolescents Regarding Blood and Organ Donation in Selected Rural Areas of Shimla, Himachal Pradesh, India (Medico Legal Update, 2020)
Objectives: The life force in all human beings, regardless of colour, race or belief, flows through their arteries and veins; it is red liquid which –depends on whether they are well or ill – bears good and bad tidings. Its various components form a highly developed defence and transport system which gives and saves life.Method: The present study was aimed to assess the knowledge and attitude regarding blood and organ donation among adolescents in selected rural areas of Shimla, Himachal Pradesh, with a view to prepare a self instructional module. The research design used for this study was Non experimental descriptive design. Non probability purposive Sampling was used to select 100 samples for the study. The tool used for the study was structured interview scheduleResult: The findings of the study includes 33% of adolescents had inadequate knowledge and 77% of adolescents had favourable attitude regarding blood and organ donation. The study revealed that there was positive correlation (r=0. 268) between the knowledge and attitude scores of blood and organ donation.Conclusion: Distributing SIM regarding blood and organ donation helps the adolescents to have adequate knowledge, awareness and positive attitude regarding blood and organ donation.